LEGAL ENGLISH IN UZBEKISTAN: TEACHING ESP FOR LAW STUDENTS AND PROFESSIONALS - Sadriddinova Nurbonu Shuxratjon qizi (Research Focus International Scientific Journal, 2025)
Legal English, as a specialized branch of English for Specific Purposes (ESP), plays a crucial role in preparing law students and professionals for the demands of global legal practice. In Uzbekistan, where legal reforms and international cooperation are rapidly evolving, the need for effective Legal English education has become increasingly significant. This study explores the teaching of Legal English in Uzbekistan, focusing on its importance, current practices, and challenges. To address these challenges, the study recommends designing ESP programs tailored to Uzbekistan’s legal context, incorporating task-based and interactive approaches, and aligning courses with international standards. The use of digital tools and cross-border collaborations is emphasized as a means to enhance learning outcomes and prepare Uzbek legal practitioners for global engagements.